Zinc sphalerite CuInSnS4 nanocrystalline materials, their preparation methods and applications

CN122895010APending Publication Date: 2026-10-13ANHUI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611106932.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,针对不同晶体物相CuInSnS4的开发与研究目前鲜少报道

Benefits of technology

[0010]本发明通过特定的方法合成出具有新型闪锌矿结构的纯相CuInSnS4纳米晶材料,实现了闪锌矿CuInSnS4纳米晶材料的选择性制备,为可见光催化剂的性能调控提供了有力手段。该闪锌矿CuInSnS4纳米晶材料用于光催化CO2还原中具有良好的催化性能,应用前景广泛。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122895010A_ABST
    Figure CN122895010A_ABST
Patent Text Reader

Abstract

The present application relates to nanocrystalline phase regulation technical field, specifically relates to a kind of sphalerite CuInSnS4 Nanocrystalline material and its preparation method and application.The present application carries out heating treatment to the dispersion system A containing monovalent copper source, tin source and indium source, and carries out calcination treatment under the introduction of the dispersion system B containing sulfur source, obtain CuInSnS4 Nanocrystalline material, wherein the sulfur source is elemental sulfur, and the phase of the CuInSnS4 Nanocrystalline material is sphalerite structure.The present application synthesizes CuInSnS4 Nanocrystalline material with new sphalerite structure, provides powerful means for the performance regulation of visible light catalyst, and the sphalerite CuInSnS4 Nanocrystalline material has good catalytic performance in photocatalytic CO2 reduction, and has wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanocrystalline phase control technology, specifically to a zincblende CuInSnS4 nanocrystalline material, its preparation method, and its applications. Background Technology

[0002] With rapid global economic development, the consumption of fossil fuels such as coal, oil, and natural gas continues to increase, leading to a continuous rise in atmospheric CO2 concentration and triggering a series of global environmental problems such as the greenhouse effect and extreme weather. Utilizing solar energy to drive photocatalytic CO2 reduction, converting the greenhouse gas CO2 into carbon-based energy fuels such as CO and CH4, is an important green technology route for achieving environmental governance and energy regeneration.

[0003] The core challenge in photocatalytic CO2 reduction lies in the difficulty of synergistically optimizing light capture and charge separation. While narrowing the band gap of materials can broaden the light absorption range, it also brings the problem of weakened redox driving forces or intensified carrier recombination. Constructing interfacial structures to promote charge separation requires sacrificing some light absorption. Therefore, simultaneously optimizing light absorption, carrier separation, and surface reaction barriers is the key challenge we currently face.

[0004] Multi-metal chalcogenides, with their tunable band structure, excellent visible light absorption, and flexible composition design, have become ideal visible light catalysts. However, it remains difficult to synergistically optimize the three indicators of light harvesting, charge separation, and surface reaction using a single material. Therefore, more refined structural control strategies are indispensable. Crystal phase engineering is a key means of regulating the photocatalytic performance of nanomaterials. Materials with the same chemical composition will exhibit vastly different atomic arrangements, band structures, and surface thermodynamic properties in different crystal phases, thus significantly affecting their photocatalytic efficiency. Currently, the phase control and structure-activity relationship of binary and ternary metal sulfides have been extensively studied, but research on the correlation between crystal phase and photocatalytic performance of quaternary metal sulfides remains scarce due to their complex cation arrangements and the difficulty of phase-selective synthesis.

[0005] Quaternary metal sulfides possess tunable electronic band structures and excellent visible light harvesting capabilities. Among them, the quaternary copper-based sulfide CuInSnS4 not only has a narrow band gap, abundant surface active sites, and high charge separation efficiency, but its conduction band potential is also compatible with the thermodynamic requirements of the CO2 reduction reaction, making it a photocatalyst of significant research value. However, the development and research of CuInSnS4 in different crystalline phases are currently rarely reported. Summary of the Invention

[0006] The purpose of this invention is to overcome the problems existing in the prior art and provide a zincblende CuInSnS4 nanocrystalline material, its preparation method, and its applications. This invention develops a novel phase structure for CuInSnS4 nanocrystalline material, providing a powerful means for the performance regulation of visible light photocatalysts.

[0007] To achieve the above objectives, the present invention provides a CuInSnS4 nanocrystalline material, wherein the phase of the CuInSnS4 nanocrystalline material is a zincblende structure.

[0008] The second aspect of the present invention provides a method for preparing CuInSnS4 nanocrystalline material, the method comprising: heating a dispersion system A containing a monovalent copper source, a tin source and an indium source, and calcining it under a dispersion system B containing a sulfur source to obtain CuInSnS4 nanocrystalline material, wherein the sulfur source is elemental sulfur, and the phase of the CuInSnS4 nanocrystalline material is zincblende structure.

[0009] A third aspect of the present invention provides the application of the above-mentioned CuInSnS4 nanocrystalline material and the CuInSnS4 nanocrystalline material prepared by the above method in photocatalytic CO2 reduction.

[0010] This invention synthesizes pure-phase CuInSnS4 nanocrystalline materials with a novel zincblende structure through a specific method, achieving selective preparation of zincblende CuInSnS4 nanocrystalline materials and providing a powerful means for performance regulation of visible light photocatalysts. These zincblende CuInSnS4 nanocrystalline materials exhibit excellent catalytic performance in photocatalytic CO2 reduction and have broad application prospects. Attached Figure Description

[0011] Figure 1 A schematic diagram of the zincblende structure of CuInSnS4 nanocrystalline material; Figure 2 The X-ray diffraction pattern of the CuInSnS4 nanocrystalline material prepared in Example 1 is shown below. Figure 3 The X-ray diffraction pattern of the CuInSnS4 nanocrystalline material prepared in Example 2 is shown below. Figure 4 The X-ray diffraction pattern of the CuInSnS4 nanocrystalline material prepared in Example 3 is shown below. Figure 5 The X-ray diffraction pattern of the CuInSnS4 nanocrystalline material prepared in Example 4 is shown below. Figure 6 The X-ray diffraction pattern of the CuInSnS4 nanocrystalline material prepared in Example 5 is shown below. Figure 7The X-ray diffraction pattern of the CuInSnS4 nanocrystalline material prepared in Example 6 is shown below. Figure 8 The X-ray diffraction pattern of CuInSnS4 nanocrystalline material prepared in Comparative Example 1 is shown below. Figure 9 The X-ray diffraction pattern of CuInSnS4 nanocrystalline material prepared in Comparative Example 2 is shown below. Figure 10 The X-ray diffraction pattern of CuInSnS4 nanocrystalline material prepared in Comparative Example 3 is shown below. Figure 11 The image shows the UV-Vis absorption spectrum of the CuInSnS4 nanocrystalline material prepared in Example 1. Figure 12 This is a schematic diagram of the electronic band structure of the CuInSnS4 nanocrystalline material prepared in Example 1; Figure 13 This is a transmission electron microscope (TEM) image of the CuInSnS4 nanocrystalline material prepared in Example 1. Figure 14 This is a transmission electron microscope image of the CuInSnS4 nanocrystalline material prepared in Example 1 at a higher resolution. Figure 15 The image shows the EDS elemental distribution of the CuInSnS4 nanocrystalline material prepared in Example 1. Detailed Implementation

[0012] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0013] The present invention provides a CuInSnS4 nanocrystalline material, wherein the phase of the CuInSnS4 nanocrystalline material is zincblende structure.

[0014] According to the present invention, the inventors, through in-depth research, synthesized CuInSnS4 nanocrystalline material with a zincblende structure. X-ray diffraction analysis of this material can determine its phase composition and crystal structure. Preferably, the CuInSnS4 nanocrystalline material exhibits characteristic peaks at 28.13°, 32.52°, 49.65°, 55.46°, 68.34°, and 75.45° in the X-ray diffraction pattern expressed as a diffraction angle 2θ.

[0015] Preferably, the average grain size of the CuInSnS4 nanocrystalline material is 3-16 nm, more preferably 6-10 nm, and can be, for example, 6.79 nm, 8.25 nm, 9.08 nm and 9.91 nm and any range between these values.

[0016] Preferably, the lattice constant of the CuInSnS4 nanocrystalline material is a=b=c=5-6Å, more preferably a=b=c=5.4-5.6Å; for example, it can be a value of 5.42Å, 5.5Å, 5.51Å and 5.6Å and any range between these values.

[0017] Preferably, the space group of the CuInSnS4 nanocrystalline material is F-43m.

[0018] Among them, such as Figure 2 As shown in the XRD pattern, the CuInSnS4 nanocrystalline material of this invention belongs to the cubic zincblende structure (F-43m space group; a=b=c=5.50509Å) and has high phase purity. Figure 1 The structural diagram shown illustrates the corresponding cubic cell structure, which exhibits a layered ABCABC atomic arrangement along the

[111] direction.

[0019] According to the present invention, the light absorption characteristics of the material play an important role in its photocatalytic activity. The band gap width not only affects the light response range of the material, but also directly affects the redox ability of the charge carriers. Preferably, the CuInSnS4 nanocrystalline material has absorption peaks in the ultraviolet-visible light absorption spectrum in the wavelength ranges of 600-700 nm and 1350-1400 nm, and the optical band gap is 1.68 eV.

[0020] According to the present invention, the band position of the material determines the redox capability of photogenerated electrons and holes, which is a key thermodynamic prerequisite for the photocatalytic reaction to occur. The position of the conduction band bottom determines the reduction capability of photogenerated electrons, and the position of the valence band top determines the oxidation capability of photogenerated holes. Preferably, the valence band top of the CuInSnS4 nanocrystalline material is 0.98 eV and the conduction band bottom is -0.7 eV.

[0021] The second aspect of the present invention provides a method for preparing CuInSnS4 nanocrystalline material, the method comprising: heating a dispersion system A containing a monovalent copper source, a tin source and an indium source, and calcining it under a dispersion system B containing a sulfur source to obtain CuInSnS4 nanocrystalline material, wherein the sulfur source is elemental sulfur, and the phase of the CuInSnS4 nanocrystalline material is zincblende structure.

[0022] According to the present invention, in order to obtain higher purity zinc sphalerite CuInSnS4 nanocrystalline material, the amounts of monovalent copper source, tin source and indium source can be adjusted. Preferably, the molar ratio of the monovalent copper source, the tin source and the indium source, calculated by each metal element, is 1:0.8-1.2:0.8-1.2, more preferably 1:0.9-1.1:0.9-1.1, for example, it can be 1:1:1, 1:0.9:1.05, 1:1:0.95 and 1:1.1:0.9 and any range between these values.

[0023] According to the present invention, the selection of precursors such as monovalent copper source, tin source and indium source has an important influence on the reaction activity and product morphology. In order to successfully and selectively prepare zincblende CuInSnS4 nanocrystalline materials, preferably, the monovalent copper source is selected from one or more of CuCl, CuI and CuBr, preferably CuCl and / or CuBr.

[0024] Preferably, the tin source is selected from one or more of Sn(acac)₂Cl₂, SnCl₄, and Sn(OAc)₄, with Sn(acac)₂Cl₂ and / or SnCl₄ being more preferred. The tin source can be provided in the form of its hydrate, for example, SnCl₄ can be provided in the form of SnCl₄·2H₂O.

[0025] Preferably, the indium source is selected from one or more of In(acac)3, InCl3, and In(NO3)3, and more preferably In(acac)3 and / or InCl3. The indium source can be provided in the form of its hydrate, for example, In(NO3)3 can be provided in the form of In(NO3)3·4H2O.

[0026] According to the present invention, the coordination ability and boiling point of the solvent used in the reaction process will affect the nucleation and crystal growth process of the nanocrystalline material. In order to better dissolve each precursor, form a stable dispersion system and provide a good reaction environment, so as to successfully obtain zinc sphalerite CuInSnS4 nanocrystalline material, preferably, the solvent of the dispersion system A is selected from one or more of oleylamine, octadecene and hexadecene, preferably oleylamine and / or octadecene.

[0027] Preferably, relative to 1 mmol of the monovalent copper source, the amount of solvent used in the dispersion system A is 50-150 mL, more preferably 80-120 mL, for example, it can be 80 mL, 100 mL, 110 mL and 200 mL and any range between these values.

[0028] According to the present invention, in order to ensure that the reaction process proceeds in an ideal direction, facilitating the subsequent nucleation and crystal growth of zincblende CuInSnS4 nanocrystalline materials and achieving higher crystallinity, preferably, the heat treatment includes heating the dispersion system A to 165-195°C. More preferably, the heat treatment includes heating the dispersion system A to 175-185°C, for example, values ​​such as 175°C, 178°C, 180°C, and 185°C, or any range between these values. Preferably, the heat treatment is carried out in a non-reactive gas atmosphere, such as nitrogen and / or argon.

[0029] According to the present invention, in order to obtain higher purity zinc sphalerite CuInSnS4 nanocrystalline material, the amount of sulfur source can be adjusted. Preferably, the molar ratio of the monovalent copper source (calculated as copper element) to the sulfur source (calculated as sulfur element) is 1:3-5, more preferably 1:3.5-4.5, for example, it can be 1:3.5, 1:3.8, 1:4 and 1:4.5 and any range between these values.

[0030] According to the present invention, sulfur source is a key reactant affecting the formation of crystal structure. Its type directly affects the nucleation rate and crystal growth process, and thus directly affects the phase structure of the product. The present invention selectively prepares CuInSnS4 nanocrystalline material with zinc sphalerite structure by using elemental sulfur as sulfur source and employing a specific method.

[0031] According to the present invention, in order to facilitate the reaction process, the solvent of the dispersion system B is preferably selected from one or more of oleylamine, octadecene, and hexadecene, and more preferably oleylamine and / or octadecene.

[0032] Preferably, the amount of solvent used in the dispersion system B is 5-20 mL relative to 1 mmol of the sulfur source, more preferably 8-16 mL, for example, values ​​such as 8 mL, 10 mL, 12 mL and 16 mL and any range between these values.

[0033] According to the present invention, by adding dispersion system B to dispersion system A at a specific temperature for calcination, and simultaneously controlling the calcination conditions, the nucleation and crystal growth processes of the system can be precisely controlled, thereby obtaining CuInSnS4 nanocrystalline material with a zincblende structure. To achieve better calcination results and higher crystallinity, preferably, the calcination conditions include: a temperature of 250-310℃ and a time of 40-80 min. More preferably, the calcination conditions include: a temperature of 270-290℃ (e.g., values ​​such as 270℃, 280℃, 285℃, and 290℃, or any range thereof), and a time of 50-70 min (e.g., values ​​such as 50 min, 60 min, 65 min, and 70 min, or any range thereof). The calcination is preferably carried out in a non-reactive gas atmosphere, such as nitrogen and / or argon.

[0034] According to the present invention, in order to obtain pure zinc sphalerite CuInSnS4 nanocrystalline material, after the calcination treatment, a post-treatment process of the reaction solution is further included. Preferably, the post-treatment includes: cooling the reaction solution (usually cooling to room temperature, for example, to 20-30°C, or appropriately exceeding this range) and then centrifuging and washing (for example, washing can be performed using suitable solvents such as n-hexane and ethanol).

[0035] A third aspect of the present invention provides the application of the above-mentioned CuInSnS4 nanocrystalline material and the CuInSnS4 nanocrystalline material prepared by the above method in photocatalytic CO2 reduction.

[0036] According to the present invention, in order to enable the zinc sphalerite CuInSnS4 nanocrystalline material to exert its photocatalytic performance and achieve better CO2 reduction effect, before using the zinc sphalerite CuInSnS4 nanocrystalline material for photocatalytic CO2 reduction, a ligand exchange process is included. Preferably, the ligand exchange includes: contacting the zinc sphalerite CuInSnS4 nanocrystalline material with amide compounds and sulfides.

[0037] According to the present invention, in order to achieve better ligand exchange effect and improve photocatalytic performance, preferably, the amount of the amide compound is 2000-4000 mmol, more preferably 2500-3500 mmol, relative to 1 mmol of the zincblende CuInSnS4 nanocrystalline material, for example, it can be 2500 mmol, 2800 mmol, 3200 mmol and 3500 mmol and any value between them.

[0038] Preferably, the amide compound is selected from one or more of formamide, N-methylpyrrolidone and N,N-dimethylformamide, and more preferably formamide and / or N-methylpyrrolidone.

[0039] Preferably, relative to 1 mmol of the zincblende CuInSnS4 nanocrystalline material, the amount of the sulfide is 20-80 mmol, preferably 30-70 mmol, for example, values ​​such as 30 mmol, 48 mmol, 55 mmol and 70 mmol and any range between these values.

[0040] Preferably, the sulfide is selected from one or more of ammonium sulfide, sodium sulfide and potassium sulfide, and more preferably ammonium sulfide and / or sodium sulfide.

[0041] According to the present invention, in order to provide a suitable reaction environment and promote ligand exchange, the solvent for the contact reaction is preferably selected from one or more of chloroform, toluene, n-hexane, cyclohexane and petroleum ether, and more preferably one or more of chloroform, toluene and n-hexane.

[0042] Preferably, relative to 1 mmol of the zincblende CuInSnS4 nanocrystalline material, the amount of solvent used in the contact reaction is 50-300 mL, preferably 100-200 mL, for example, it can be 100 mL, 140 mL, 180 mL and 200 mL and any range between these values.

[0043] According to the present invention, in order to improve reaction efficiency, preferably, the conditions for the contact reaction include: a temperature of 10-40°C and a time of 2-6 hours. More preferably, the conditions for the contact reaction include: a temperature of 20-30°C (e.g., values ​​such as 20°C, 22°C, 25°C, and 30°C, or any range thereof), and a time of 3-5 hours (e.g., values ​​such as 3 hours, 3.5 hours, 4 hours, and 5 hours, or any range thereof). Preferably, the contact reaction is carried out in a non-reactive gas atmosphere, such as nitrogen and / or argon.

[0044] According to the present invention, after the above-mentioned contact reaction is completed, a first post-treatment process may be included to obtain a product with better properties and purity. Preferably, the first post-treatment includes: taking the upper layer solution after the reaction solution is separated into layers and centrifuging and washing it (for example, washing can be performed using suitable solvents such as water and ethanol).

[0045] This invention synthesizes pure-phase CuInSnS4 nanocrystalline materials with a novel zincblende structure through a specific method, achieving selective preparation of zincblende CuInSnS4 nanocrystalline materials and providing a powerful means for performance regulation of visible light photocatalysts. These zincblende CuInSnS4 nanocrystalline materials exhibit excellent catalytic performance in photocatalytic CO2 reduction and have broad application prospects.

[0046] The present invention will be described in detail below through embodiments.

[0047] In the following examples, the apparatus used is conventional in the art, the operations performed are conventional in the art, and the raw materials and reagents used are commercially available.

[0048] Example 1 Under an argon atmosphere, 0.1 mmol of CuCl, 0.1 mmol of Sn(acac)₂Cl₂, and 0.1 mmol of In(acac)₃ were added to 10 mL of oleylamine. The reaction solution was heated to 180 °C, and 5 mL of an oleylamine solution containing elemental sulfur (0.4 mmol of elemental sulfur) was added. The reaction solution was then heated to 280 °C and calcined for 60 min to grow nanocrystals. After the reaction was completed, the reaction solution was allowed to cool naturally to room temperature and centrifuged. The resulting solid product was washed with n-hexane and ethanol, respectively, to obtain CuInSnS₄ nanocrystalline material.

[0049] Example 2 Under an argon atmosphere, 0.1 mmol of CuBr, 0.095 mmol of SnCl4·2H2O, and 0.11 mmol of InCl3 were added to 8 mL of octadecene. The reaction solution was heated to 175 °C, and 4 mL of an octadecene solution of elemental sulfur (0.45 mmol of elemental sulfur) was added. The reaction solution was then heated to 290 °C and calcined for 70 min to grow nanocrystals. After the reaction was completed, the reaction solution was allowed to cool naturally to room temperature and centrifuged. The obtained solid product was washed with n-hexane and ethanol, respectively, to obtain CuInSnS4 nanocrystalline material.

[0050] Example 3 The method of Example 1 differs in that the reaction solution is heated to 165°C before the addition of an oleylamine solution containing elemental sulfur, ultimately yielding CuInSnS4 nanocrystalline material.

[0051] Example 4 The method of Example 1 differs in that the reaction solution is heated to 195°C before the addition of an oleylamine solution containing elemental sulfur, ultimately yielding CuInSnS4 nanocrystalline material.

[0052] Example 5 The method is the same as in Example 1, except that the calcination temperature is 250°C, and CuInSnS4 nanocrystalline material is finally obtained.

[0053] Example 6 The method is the same as in Example 1, except that the calcination temperature is 310°C, and CuInSnS4 nanocrystalline material is finally obtained.

[0054] Comparative Example 1 The method of Example 1 is the same, except that elemental sulfur is replaced with an equimolar amount of thioacetamide, and CuInSnS4 nanocrystalline material is finally obtained.

[0055] Comparative Example 2 The method of Example 1 is different except that elemental sulfur is replaced with an equimolar amount of dodecanethiol, and CuInSnS4 nanocrystalline material is finally obtained.

[0056] Comparative Example 3 The method of Example 1 differs in that the reaction solution was not heated before adding the oleylamine solution of elemental sulfur, but the oleylamine solution of elemental sulfur was directly added to the reaction solution to finally obtain CuInSnS4 nanocrystalline material.

[0057] Test Example 1 The CuInSnS4 nanocrystalline material prepared in Example 1 was subjected to X-ray diffraction analysis, and the obtained X-ray diffraction pattern is shown below. Figure 2 As shown, the material exhibits characteristic peaks at 28.13°, 32.52°, 49.65°, 55.46°, 68.34°, and 75.45°, with lattice constants of a=b=c=5.50509Å and space group F-43m, confirming its phase structure as zincblende. A schematic diagram of the structure is shown below. Figure 1 As shown, the average grain size of the nanocrystals was determined to be 6.79 nm through high-resolution transmission analysis.

[0058] X-ray diffraction analysis was performed on the CuInSnS4 nanocrystalline materials prepared in Examples 2-6. The X-ray diffraction patterns of the CuInSnS4 nanocrystalline materials prepared in Examples 2-6 are shown below. Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 As shown, the CuInSnS4 nanocrystalline materials prepared in Examples 2-6 have the same characteristic peaks as those in Example 1, proving that their phase structure is a zincblende structure.

[0059] X-ray diffraction analysis was performed on the CuInSnS4 nanocrystalline materials prepared in Comparative Examples 1-3. The X-ray diffraction patterns obtained for each are shown below. Figure 8, Figure 9 and Figure 10 As shown, the CuInSnS4 nanocrystalline materials prepared in Comparative Examples 1-3 exhibit characteristic peaks at 26.38°, 27.83°, 29.91°, 38.49°, 46.73°, 50.49°, 55.19°, 62.84°, and 71.25°, which are consistent with the characteristic peaks of the wurtzite structure, proving that the prepared CuInSnS4 nanocrystalline materials have a wurtzite structure.

[0060] The test results above show that Examples 1-6 using the technical solution of the present invention can selectively prepare CuInSnS4 nanocrystalline materials with a zincblende structure, while Comparative Examples 1-3 using a non-technical solution of the present invention can only prepare CuInSnS4 nanocrystalline materials with a wurtzite structure.

[0061] Test Example 2 The zincblende CuInSnS4 nanocrystals prepared in Example 1 were subjected to UV-Vis absorption spectroscopy. The testing procedure was as follows: 15 mg of zincblende CuInSnS4 nanocrystals were dispersed in 1 mL of n-hexane. After ultrasonic dispersion, 1 mL was transferred to a cuvette. Using n-hexane as a reference, the absorption spectrum was recorded in the wavelength range of 600-1400 nm using a UV-Vis spectrophotometer. The obtained UV-Vis absorption spectrum is shown below. Figure 11 As shown, the zincblende CuInSnS4 nanocrystalline material exhibits absorption peaks in the ultraviolet-visible absorption spectrum within the wavelength ranges of 600-700 nm and 1350-1400 nm, with an optical band gap of 1.68 eV.

[0062] The zincblende CuInSnS4 nanocrystalline material prepared in Example 1 was subjected to ultraviolet photoelectron spectroscopy (UPS) testing. The testing procedure was as follows: 10 mg of zincblende CuInSnS4 nanocrystalline material was dispersed in 6 mL of chloroform, and after being ultrasonically dispersed evenly, 50 mL of the dispersion was dropped into 5 mL of chloroform. A uniform thin film was formed on a 5mm silicon wafer for testing. The resulting electronic band structure schematic is shown below. Figure 12 As shown, the valence band top of the zincblende CuInSnS4 nanocrystalline material is 0.98 eV and the conduction band bottom is -0.7 eV.

[0063] The zincblende CuInSnS4 nanocrystalline material prepared in Example 1 was analyzed using transmission electron microscopy (TEM). The obtained TEM images are shown below. Figure 13 As shown, the transmission electron microscope image at a higher resolution is as follows: Figure 14As shown, the zincblende CuInSnS4 nanocrystalline material consists of cubic particles with a relatively uniform particle size distribution and an average particle size of approximately 6.79 nm. High-resolution transmission electron microscopy (HRTEM) images reveal clear lattice fringes in the nanocrystals, indicating that the obtained product is a well-crystallized zincblende CuInSnS4 nanocrystalline material.

[0064] Energy-dispersive X-ray spectroscopy (EDS) was performed on the zincblende CuInSnS4 nanocrystalline material prepared in Example 1. The resulting EDS elemental distribution map is shown below. Figure 15 As shown, the distribution range of each element is consistent and uniform.

[0065] Application examples The CuInSnS4 nanocrystalline materials prepared in Examples 1-6 and Comparative Examples 1-3 were subjected to ligand exchange. The resulting products were dispersed in water, uniformly filtered onto the surface of a quartz fiber membrane, and then placed in a reactor. CO2 was introduced for 20 min to remove air from the reactor. The reactor was then irradiated with a 300W xenon lamp (λ=350-780nm) for 4 h. 1 mL of the product gas was injected into a gas chromatograph every hour for analysis. The test results are shown in Table 1.

[0066] The ligand exchange process is as follows: Under an argon atmosphere, 0.07 mmol of CuInSnS4 nanocrystals were dissolved in 10 mL of chloroform, followed by the addition of 226 mmol of formamide and 3.4 mmol of ammonium sulfide. The reaction was carried out at 25 °C for 4 h. After the reaction was completed, the upper formamide solution after separation was centrifuged, and the resulting solid was washed with water and ethanol, respectively, to obtain the product.

[0067] Table 1

[0068] As shown in Table 1, the wurtzite CuInSnS4 nanocrystalline materials obtained using the technical solutions of this invention in Examples 1-6 exhibit better photocatalytic performance. In contrast, the wurtzite CuInSnS4 nanocrystalline materials with poorer crystallinity obtained in Comparative Examples 1-3 show poorer photocatalytic performance.

[0069] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A CuInSnS4 nanocrystalline material, characterized in that, The CuInSnS4 nanocrystalline material has a zincblende structure.

2. The CuInSnS4 nanocrystalline material according to claim 1, wherein, The CuInSnS4 nanocrystalline material exhibits characteristic peaks at 28.13°, 32.52°, 49.65°, 55.46°, 68.34°, and 75.45° in the X-ray diffraction pattern expressed as a diffraction angle 2θ. And / or, the average grain size of the CuInSnS4 nanocrystalline material is 3-16 nm, preferably 6-10 nm; And / or, the lattice constant of the CuInSnS4 nanocrystalline material is a=b=c=5-6Å, preferably a=b=c=5.4-5.6Å; And / or, the space group of the CuInSnS4 nanocrystalline material is F-43m.

3. The CuInSnS4 nanocrystalline material according to claim 1 or 2, wherein, The CuInSnS4 nanocrystalline material exhibits absorption peaks in the ultraviolet-visible absorption spectrum within the wavelength ranges of 600-700 nm and 1350-1400 nm, and has an optical band gap of 1.68 eV.

4. The CuInSnS4 nanocrystalline material according to any one of claims 1-3, wherein, The CuInSnS4 nanocrystalline material has a valence band top of 0.98 eV and a conduction band bottom of -0.7 eV.

5. A method for preparing CuInSnS4 nanocrystalline material, characterized in that, The method includes: heating a dispersion system A containing a monovalent copper source, a tin source, and an indium source, and then calcining it under a dispersion system B containing a sulfur source to obtain CuInSnS4 nanocrystalline material, wherein the sulfur source is elemental sulfur, and the phase of the CuInSnS4 nanocrystalline material is zincblende structure.

6. The method according to claim 5, wherein, The molar ratio of the monovalent copper source, the tin source, and the indium source, calculated by each metal element, is 1:0.8-1.2:0.8-1.2, preferably 1:0.9-1.1:0.9-1.1; And / or, the monovalent copper source is selected from one or more of CuCl, CuI and CuBr, preferably CuCl and / or CuBr; And / or, the tin source is selected from one or more of Sn(acac)2Cl2, SnCl4 and Sn(OAc)4, preferably Sn(acac)2Cl2 and / or SnCl4; And / or, the indium source is selected from one or more of In(acac)3, InCl3 and In(NO3)3, preferably In(acac)3 and / or InCl3; And / or, the solvent of the dispersion system A is selected from one or more of oleylamine, octadecene and hexadecene, preferably oleylamine and / or octadecene; And / or, relative to 1 mmol of the monovalent copper source, the amount of solvent used in the dispersion system A is 50-150 mL, preferably 80-120 mL.

7. The method according to claim 5 or 6, wherein, The heat treatment includes heating the dispersion system A to 165-195°C; more preferably, the heat treatment includes heating the dispersion system A to 175-185°C.

8. The method according to any one of claims 5-7, wherein, The molar ratio of the monovalent copper source (calculated as copper element) to the sulfur source (calculated as sulfur element) is 1:3-5, preferably 1:3.5-4.5; And / or, the solvent of the dispersion system B is selected from one or more of oleylamine, octadecene and hexadecene, preferably oleylamine and / or octadecene; And / or, relative to 1 mmol of the sulfur source, the amount of solvent used in the dispersion system B is 5-20 mL, preferably 8-16 mL.

9. The method according to any one of claims 5-8, wherein, The calcination conditions include a temperature of 250-310℃ and a time of 40-80 min; more preferably, the calcination conditions include a temperature of 270-290℃ and a time of 50-70 min.

10. The application of the CuInSnS4 nanocrystalline material according to any one of claims 1-4 and the CuInSnS4 nanocrystalline material prepared by the method according to any one of claims 5-8 in photocatalytic CO2 reduction.